Artificial Intelligence: A Primer for the Radiologists - Bhatia, Harsimran; Bhatia, Anmol; Ahuja, Chirag K.; Singh, Arnavjit; Sodhi, Kushaljit S. (Indographics, 2022)
Artificial intelligence (AI) has revolutionized almost every sphere of life today by providing cutting-edge tools aimed at improving the quality of life. The term AI refers to any operating system or a software that mimics human intelligence and performs functions like the human mind with minimal human intervention. The present review article focuses on the basics of AI and the terminology used in the field of AI. Flowcharts and figures to facilitate easy understanding of its impact and its potential applications have also been provided. It is meant to serve as a primer for the beginner.
Keywords: artificial intelligence; learning; machine; deep